Hazard identification, risk assessment and risk control: a study at construction site - Abd Latip, Muhammad Faris; Abdullah, Muhammad Arif; Khalid, Amir; Jaat, Norrizam; Ngadiron, Zuraidah; Zaman, Izzuddin (Penerbit UTHM, 2020)
Occupational Safety and Health Act (OSHA) is an Act to make further provisions for securing the safety, health and welfare of persons at work, for protecting others against risks to safety or health in connection with the activities of persons at work, to establish the National Council for Occupational Safety and Health, and for matters connected therewith. This study focuses on infrastructure construction in Pagoh Education Hub. In present days, despite of knowledge in OSHA act, workers often proceed the work without considering any safety precaution or act at workplace as stated in OSHA Act. Due to ignorance of workers and employee on OSHA Act, workers are exposed to danger and hazard at their workplace causing them minor or worst fatal injury. The data collection was carried out through site investigation using Preliminary Hazard Analysis (PHA), HIRARC form and interview session with several workers in the constructio. The main objective of this study is to support the idea to coordinate and redefined the practice of occupational safety and health as workers discipline at their workplace based on existing potential hazard. This study was conducted to identify the hazard that occur at the workplace and analyse the safety precaution taken by the workers and employer to avoid accidents. As a result, this study listed several suggestions to improve the practice of occupational safety and health among workers in the workplace.